Implementation of Dijkstra's algorithm to find an effective route to avoid traffic jam on a busy hour - Sembiring, P; Harahap, A S; Zalukhu, K S (Journal of physics. Conference series, 2018)
Traffic Jam is a well-known thing that occurs in Indonesia, which caused by some factors, such as vehicle volume, narrow road, road user, activity on the road, and many more. Dijkstra's Algorithm is an algorithm that is commonly used in pathfinding to find a shortest path (Shortest Path Problem). Main focus on this research is to find an effective route to avoid the traffic jam points. This algorithm works to find the route to the final destination, finding the shortest route, and then to eliminate the route which qualified to the traffic jam. The result is an effective route, which is a route that has a possible shortest route and has no traffic jam points.